ANTIULCER ACTIVITY OF AGNIMUKHA CHURNA - Prakash Rao, S.; Amrit, Indu; Jain, Parag; Singh, Vijay (International Journal of Ayurveda and Pharma Research, 2015)
Background: Agnimukha Churna is a popular Ayurvedic formulation, composed of herbs and spices, used for treatment of gastrointestinal disorders by traditional healers. Objectives: In present study, we have to subject the pharmacognostic, phytochemical test and to evaluate the anti-ulcer activity of Agnimukha Churna. Material and Methods: Study was carried out, by using two methods i.e., ethanol induced ulcers (5ml/kg, Absolute ethanol) and aspirin induced ulcers (200mg/kg) in rats pretreated with the doses of, Alcoholic Extract of Churna (AEC) (200mg/kg), Hydro-alcoholic Extract of Churna (HAEC) (200mg/kg), Ranitidine (20mg/kg). After 1 hour in ethanol induced method and 4 hour in aspirin induced method rat was sacrificed and stomach was removed for observation of ulcer scores, ulcer index and percentage of inhibition. Results: The AEC and HAEC maintain the integrity of gastric mucosa by virtue of its effect on offensive and defensive gastric mucosal factors. AEC and HAEC significantly (P<0.0001) decreased ulcer index in ethanol induced and aspirin induced model. Conclusions: Cyto-protective action may be the major mechanism responsible for the present study, which cause the generation of prostaglandins promoting inhibition of ulcer. Our study shows that Agnimukha churna and their fractions have the potential to be used as an anti-ulcer.